2007
DOI: 10.1002/bit.21771
|View full text |Cite
|
Sign up to set email alerts
|

Influence of ammonium chloride feeding time and light intensity on the cultivation of Spirulina (Arthrospira) platensis

Abstract: This study dealt with the influence of both the feeding time and light intensity on the fed-batch culture of the cyanobacterium Spirulina (Arthrospira) platensis using ammonium chloride as a nitrogen source. For this purpose, a 2(2) plus star central composite experimental design combined with response surface methodology was employed, and the maximum cell concentration (X(m)), the cell productivity (P(X)), and the yield of biomass on nitrogen (Y(X/N)) were selected as the response variables. The optimum value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
38
2
17

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 51 publications
(65 citation statements)
references
References 35 publications
8
38
2
17
Order By: Relevance
“…• C, U = 1.879 mmol L −1 d −1 ) was the likely result of partial loss of urea as ammonia during cultivation, 38 favored by the relatively high temperature, hence the consequent limitation of growth (X m = 2201 mg L −1 ). As pointed out in previous work carried out in open pond with the same nitrogen source, the adoption of a temperature significantly higher than the optimum for the A. platensis strain employed in this study (29 • C) 15 could have been responsible for thermal inactivation of the growth like that observed for other microorganisms.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…• C, U = 1.879 mmol L −1 d −1 ) was the likely result of partial loss of urea as ammonia during cultivation, 38 favored by the relatively high temperature, hence the consequent limitation of growth (X m = 2201 mg L −1 ). As pointed out in previous work carried out in open pond with the same nitrogen source, the adoption of a temperature significantly higher than the optimum for the A. platensis strain employed in this study (29 • C) 15 could have been responsible for thermal inactivation of the growth like that observed for other microorganisms.…”
Section: Resultsmentioning
confidence: 99%
“…To this purpose we used the statistical methodology described in the Materials and methods section. However, the optimization of X m required an expansion of the experimental design as suggested by Fratelli et al 43 and Bezerra et al 38 ; therefore, additional experiments (runs 12-23) were carried out, whose results are illustrated in Fig. 2 and summarized in Table 1, part B.…”
Section: Multivariable Regression Analysismentioning
confidence: 99%
“…In conventional cyanobacteria cultivation, nitrate salts (sodium and potassium nitrates) are the most used nitrogen sources, and several studies have demonstrated the feasibility of replacing these conventional nitrogen sources with low-cost alternatives such as urea, ammonium sulfate and ammonium chloride Bezerra et al, 2008;Matsudo et al, 2012;Ferreira et al, 2010;AvilaLeon et al, 2012). Depending on the purpose of cultivation (e.g., pigments, carotenoid, fatty acids, biomass), different variables may be controlled in the growth of A. platensis.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the quantity and quality of the nitrogen source have a significant effect on the biomass yield and quality (Piorreck et al, 1984;Danesi et al, 2002;Avila-Leon et al, 2012). Under alkaline conditions, such as those usually adopted in S. platensis production, ammonium salts are in part present in the medium as ammonia, which is volatile and can even be toxic to the microorganism, depending on its concentration (Abeliovich & Azov, 1976;Muro-Pastor & Florencio, 2003;Bezerra et al, 2008). Even when urea is used as a nitrogen source, ammonia is formed either by its hydrolysis under alkaline conditions (Danesi et al, 2002) or by urease activity (Shimamatsu, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation